Transition Metal‐Catalyzed Enantioselective C−H Functionalization via Chiral Transient Directing Group Strategies - Liao, Gang; Zhang, Tao; Lin, Zhi‐Keng; Shi, Bing‐Feng (Angewandte Chemie International Edition, 2020)
Transition metal‐catalyzed enantioselective functionalization of C−H bond, the most abundant functionality in organic molecules, has emerged as an expedient synthetic approach to streamline the synthesis of complex chiral molecules. Despite significant progress, traditional directing group‐enabled strategies require additional steps for the installation and removal of directing groups from the target molecule. The recently developed asymmetric C−H functionalization using chiral transient directing groups (cTDGs) offers a promising alternative that can circumvent this obstacle and therefore simplify the process. In this Minireview, we briefly discuss the advent and recent advances of this emerging concept, with an emphasis on discussing the creation of various stereogenic centers and the developments of cTDGs. Applications in natural product synthesis and ligand derivatizations are also discussed. We hope this Minireview will highlight the great potential of this strategy and help to inspire further endeavors. Chiral transient directing group (cTDG) strategies give rise to fundamentally new concepts in asymmetric C−H activation and enable the synthesis of chiral molecules without the need of pre‐installation and removal of directing groups. This Minireview provides an overview of recent advances in cTDG for the construction of chiral compounds with different types of chirality.